Caracterização e conservação de sementes de espécies da subtribo Hyptidinæ (Lamiaceae) nativas de semiárido baiano - Ferraz, Marisol (2016)
The caatinga is a biome with great biological diversity, endemism and big potential for the production of bioactive compounds of economic interest, but with a great lack of information about the vegetal species and their forms of conservation. This work in order to reduce this gap and ensure their genetic conservation, eight species of subtribe Hyptidinae (Lamiaceae): Eplingiella fruticosa (Salzm. ex Benth.) Harley & J.F.B.Pastore, Gymneia platanifolia (Salzm. ex Benth.) Harley & J.F.B.Pastore, Hyptis lanceolata Poir., Hyptis ramosa Pohl ex Benth., Hyptis velutina Pohl ex Benth., Martianthus leucocephalus (Salzm. ex Benth.) J.F.B.Pastore, Mesosphaerum pectinatum (L.) Kuntze, Mesosphaerum suaveolens (L.) Kuntze., the seeds was characterized, the mucilage was extracted and the storage was done for twenty-four months in four different environments: 10 ° C without humidity control, to 10 ° C and 25 ° C with zinc chloride saturated solution, in liquid nitrogen at -196 ° C. The germinative response was tested every three months to evaluate storage efficiency in seed conservation. The efficiency of the use of X-ray image in the evaluation of the quality of the stored seeds was tested. The moisture content of the seeds ranged from 1.98% to 8.05%, suitable for storage. E. fruticosa, M. pectinatum and M. suaveolens can be good sources of mucilage due to their high yield. The environments with low relative humidity (5.5%) maintained by zinc chloride were efficient in the storage of the seeds of five of the eight evaluated species. X-ray image analysis is effective in evaluating seed quality.